Developing Prototype Simulants for Surface Materials and Morphology of Near Earth Asteroid 2016 HO3 - Xiaojing Zhang (American Association for the Advancement of Science (AAAS), 2021)
There are a variety of applications for asteroid simulants in asteroid studies for science advances as well as technology maturation. For specific purpose, it usually requires purpose-specialized simulant. In this study, we designed and developed a set of prototype simulants as S-type asteroid surface materials analogue based on H, L, and LL ordinary chondrites’ mineralogy and terrestrial observations of near-earth asteroid 2016 HO3, which is the Chinese sample return mission target. These simulants are able to simulate morphology and reflectance characteristics of asteroid (469219) 2016 HO3 and, thus, to be used for engineering evaluation of the optical navigation system and the sampling device of the spacecraft during the mission phase. Meanwhile, these prototype simulants are easily to modify to reflect new findings on the asteroid surface when the spacecraft makes proximate observations.